PSXII-3 Postparturient immunoglobulin variations in mammary quarters and its repeatability in sequential lactations of Dromedary camel. (7th December 2018) - Ahmadpour, A; Zarrin, M; Christensen, R; Osouli, S
Abstract: Whole immunoglobulin G (IgG) content of camel colostrum is documented, whereas the quarter differences in IgG content of camel colostrum is still unknown. The present investigation was carried out to examine variations in quarter colostrum characteristics in consecutive lactations as well as the IgG concentration of camel colostrum. Animals were fed all year around by grazing and were provided with mineral blocks. Colostrum was collected quarter wise every hour for the first 12 h after parturition from 17 primiparous dromedary camels and their next consecutive lactation. The IgG concentration (g/L) was measured using ELISA after performing a validation procedure by standard addition method. Data was analyzed using MIXED procedure of SAS. Comparing two time points, the IgG concentration at first lactation and second at the time of delivery was 66.99 ± 11.1(g/L; mean ± SD), and 72.76 ± 12.6, and by 12 h postpartum it decreased to 47.36 ± 10.4, and 49.67 ± 10.2, respectively (P < 0.05). Colostrum yield and concentration showed a high variation between first and second parity (P = 0.03). Whole immunoglobulin G for camel and quarter (camel) were different in both total IgG yield and concentration per quarter (P < 0.05). However interclass coefficient (ICC) for total IgG yield was found to be similar in camels from first and second lactation (ICC = 0.38). Mean IgG concentration of the front and rear quarters had no difference. This difference in IgG content of quarter-collected colostrum suggests that although the circulatory hormones and precursors for colostrogenesis may reach the glands similarly, each gland has its own pattern and capacity to accumulate the IgG. This finding also supports the theory that local action of autocrine, paracrine, epigenetic and gene regulation systems most likely act on camel's colostrogenesis ability, which has previously been documented for dairy cows.